Leopard Seals (Hydrurga leptonyx) in New Zealand Waters Predating on Chondrichthyans - van der Linde, Krista; Visser, Ingrid N.; Bout, Rick; Lalas, Chris; Shepherd, Lara; Hocking, David; Finucci, Brittany; Fyfe, Jim; Pinkerton, Matthew (Frontiers in Marine Science, 2021)
Leopard seals (Hydrurga leptonyx) are top-order predators that prey on a wide variety of species including crustaceans, cephalopods, fishes, birds, and pinnipeds. While multiple diet studies have been conducted worldwide, there are no previous accounts of leopard seals predating on chondrichthyans. As part of a wider study on the diet of leopard seals in New Zealand (NZ) waters, researchers and citizen scientists recorded 39 observations of predation and collected 127 scats (166 total records) between 1942 and 2019. Predation on chondrichthyans was detected in 23.1% (n = 9) of observations of predation and 7.1% (n = 9) of scats (the latter via morphological examination and DNA sequencing). From both observations of predations and scats, three chondrichthyan species or genus were identified; elephantfish (Callorhinchus milii), ghost sharks (Hydrolagus spp.) and spiny dogfish (Squalus acanthias). While this is the first published record of leopard seals feeding on chondrichthyans, the relatively high frequency of occurrence within our NZ records, and that certain individuals appeared to target this type of prey, indicates that these species could constitute a substantial, or important, part of the diet for some leopard seals in this region. As chondrichthyans form an important part of the NZ marine ecosystems, our recognition of an additional top-order predator of these species contributes to understanding the overall health of, and future impacts of predators on, the wider NZ marine ecosystem.